Noise and vibration analysis for automotive radiator cooling fan - N. F. D., Razak; M. S. M., Sani; Azmi, W. H.; Zhang, B. (Institute of Physics Publishing, 2017)
This paper presents to analyse the noise and vibration of automotive radiator specifically focused on its cooling fan for different fan condition and different coolants use which are Ethylene Glycol (EG) water-based and Titanium Oxide (TiO2) nanofluid. Noise source identification is carried out by utilizing sound intensity mapping method while an accelerometer is used in order to measure the vibration results. Both of these experiments are conducted when the fan was in static and working conditions. The maximum cooling fan speed for working fan detected by a tachometer for EG water based is 1990 rpm while TiO2 nanofluid is 2030 rpm. The speed is different due to the different physical properties such viscosity of each coolant have where TiO2 nanofluid has lower viscosity than EG water-based. The maximum sound power level produced by EG water-based is 53.73 dB while TiO2 nanofluid is 101.94 dB. Meanwhile, the vibration frequencies of EG water-based are higher than TiO2 nanofluid. The noise level is increasing with cooling fan speed but decreasing the vibration frequency. Other than study the noise and vibration of automotive radiator, this research also analyzed the potential application by using nanofluid due to its many great properties according to its major use in heat transfer enhancement. As conclusion, nanofluid as a radiator coolant could improve of heat transfer rate, but also could reduce the presence of vibration in automotive cooling system